Rättslig operationalisering av företags samhällsansvar : Särskilt om avtalsrätt, köprätt, konsumentköprätt, marknadsföringsrätt och aktiebolagsrätt - Halje, Lovisa (Uppsala universitet, 2022)
The main objective of this thesis is to explore and describe the possibilities for legal operationalization of CSR in contract law, sales law and consumer sales law, marketing law and company law. A supplementary aim is to identify regulation on and illustrate the regulatory context of CSR. The illustration provides a background and a framework for the main objective of the study, as well as confirms the legal relevance of CSR. Legal operationalization of CSR requires that CSR is anchored in law and that there are mechanisms for enforcement available. In contract law, CSR is legally anchored when a CSR condition follows from a contract. In a Swedish sales law context, legal anchoring takes place when a buyer’s expectation regarding CSR is not met and this is considered a defect, fel. From a marketing law point of view, the possibilities to consider a CSR statement an unfair commercial practice are relevant. In a company law context, CSR is legally anchored when included in the articles of association, in an instruction from the general meeting or the board, in the board’s internal guidelines or in the remuneration guidelines of the company. In all, contract parties, shareholders and the board are “strong” legal subjects, in that they are able to proactively formulate and anchor CSR norms in law. In company law, the understanding of the company’s interest and purpose, as well as the business case for CSR and the understanding of profit create borders within which the company law operationalization of CSR functions. Sales law and marketing law offer retroactive tools to market actors. The possibilities to anchor CSR in marketing law are vast, whereas the applicability of the sales law rules to a large extent is dependent on the connection between the (failed) CSR expectation and the sold goods. The remedies in the explored areas of law typically do not protect the CSR interest in question directly.
Keywords: Aktiebolagsrätt; Avtalsrätt; CSR; Company law; Contract law; Corporate Social Responsibility; Corporate sustainability; Företags samhällsansvar; Förrättsligande; Hållbarhet; Hållbart företagande; Juridification; Konsumentköprätt; Köprätt; Legal operationalization; Legalization; Marketing law; Marknadsföringsrätt; Private law; Privaträtt; Rättslig operationalisering; Sales law; Sustainability

Avtalets räckvidd I : Om avtals tredjemansverkningar, särskilt vid tredjemansavtal och direktkrav - Mossberg, Oskar (Iustus förlag, 2020)
The idea that a contract should affect other people than the parties has seemingly always been a provocative notion. A contract binds the contracting parties – and only them – together in a legal relationship, and yet according to contemporary law a contract can have various legal effects for third parties, i.e. non-parties. The parties can conclude a contract for the benefit of a third party, and third parties can be affected by the contracts of others pursuant to both statutory law and uncodified general principles of law. The legal theme of contractual third party effects involves both theoretical and practical challenges. This doctoral dissertation addresses a number of these challenges, by examining (mainly) Swedish and Nordic private law sources. The study explores third party contracts and direct claims, as well as the relationship between these two legal figures, by placing them in a historical and theoretical context and by performing a series of contextualizing readings of sources revealing developments in both case law and legal scholarship. The research is based on a legal scientific methodology, enriched by theoretical and methodological imports pillaged from the classical teachings and contemporary scholarship on rhetoric. The result can be characterized as a form of rhetorically infused, topically oriented, hermeneutic study of contemporary legal discourse on third party effects of contract.
Keywords: Avtalsrätt; Contract law; Direct claims; Direktkrav; Retorisk hermeneutik; Third parties; Third party contracts; Third party effects; Topisk retorik; Tredjemansavtal

Diskrimineringsansvar : En civilrättslig undersökning av förutsättningarna för ansvar och ersättning vid diskriminering - Hellborg, Sabina (Iustus förlag, 2018)
This doctoral thesis examines liability for discrimination under Swedish private law. According to chapter 5, section 1 of the Swedish Discrimination Act (diskrimineringslagen) compensation shall be paid by natural or legal persons who violate the prohibitions of discrimination that are established in the act. The purpose of the compensation is not only to compensate the person discriminated against for the violation of the right to equal treatment, but also to prevent further discrimination. The thesis examines two main questions: (i) what preconditions need to be fulfilled in order to establish liability for discrimination? and (ii) what circumstances affect the amount of compensation? An overarching aim of the thesis is to create an understanding of the characteristic problems and questions that occur when handling discrimination-related questions in a private law context. Consideration is taken to the EU law background and the aim, articulated in EU directives, to achieve effective, proportionate and dissuasive remedies for breaches of the principle of equal treatment. The research focuses on the prohibitions applicable in the working life and regarding goods, services and housing. It includes detailed analyses of the prohibitions against direct discrimination, indirect discrimination, inadequate accessibility, harassment and sexual harassment. The analyses deal with questions concerning the subjective motives of the discriminating party, problematic aspects considering the burden of proof as well as the exceptions from the prohibitions. Circumstances affecting the amount of compensation are analysed considering the character of the discriminating behaviour and its effects. Certain aspects attributable to the preventive function of the damages are examined, as well as how they have been decisive in the court judgements.
Keywords: Ansvarsrätt; Diskriminering; Diskrimineringsersättning; Kränkning; Skadestånd; Skadeståndsrätt; Trakasserier

Institutionella samspel : Om möten mellan en kommersiell och en ideell logik - Kvarnstrom, Emilia (Företagsekonomiska institutionen, Uppsala universitet, 2016)
Institutional logics create order and stability. They organize interaction and prescribe how we should behave towards each other. Such logics have generally been regarded as exclusive, in the sense that an organizational field is always guided by a single institutional logic. If there are two or more institutional logics in one setting at the same time this will create conflicting demands and contradictions. So how do organizations and individuals that act in these settings, where different institutional logics do meet, cope with the conflicting demands? This question is researched by studying actors who organize partnerships between corporations and non-profit organizations. Institutional logics have typically been studied at field level. My study follows a more recent literature strand focusing on individuals and their way of coping with conflicting institutional logics. In this thesis, interviews, text analysis and observations are used. The interviews were conducted with CSR managers of corporations, managers of corporate partners at non-profit organizations, CSR consultants, and project managers of intermediary organizations. These actors are working in an environment where conflicting institutional logics are played out. Using a narrative approach it is shown how these actors are aware of their institutional environment and its conflicts which requires them to constantly act as translators. The study shows that the actors organize an interplay between a market-logic and a social-welfare logic by bringing together the logics and establishing limits to what extent logics can be mixed. Thus, the actors can be understood as bilingual, rather than hybrids. Furthermore, it is argued that a narrative approach provides the possibility to understand institutional logics in empirical contexts as more present and visible than they are usually considered to be. The study concludes that bilingual actors balance conflicting demands and negotiate requirements set by institutional logics in their day-to-day work. Settings where institutional logics meet can hence be understood as both a contradiction and an ongoing interplay.
Keywords: Actor; Cross-sectoral partnerships; Hybrid organization; Institutional logics; Institutional theory; Narrative; Partnerships

Ömsesidiga överenskommelser enligt skatteavtal - Sallander, Ann-Sophie (Jönköping International Business School, 2013)
Ömsesidiga överenskommelser (eng. mutual agreement procedures) återfinns huvudsakligen i artikel 25 OECD:s modellavtal. Syftet med sådana överenskommelser är att undvika internationell dubbelbeskattning. Överenskommelserna kan antingen utgöra ett rättsmedel, som är ett alternativ till domstolsförfarande, eller verka som ett medel för att få skatteavtalen att fungera bättre mellan de avtalsslutande staterna. De rättsliga svårigheter som uppkommer i samband med överenskommelserna beror huvudsakligen på att överenskommelserna utgör en internationellt, av OECD, konstruerad företeelse som ska anpassas till och tillämpas på ett nationellt, redan befintligt regelsystem. Det kan härmed uppkomma spänningar och motsättningar mellan olika bestämmelser. Det övergripande syftet med denna studie är att kartlägga och utvärdera en internationellt konstruerad företeelse, dvs. ömsesidiga överenskommelser, för att undersöka om ändamålet med sådana överenskommelser uppfylls inom ramen för det svenska regelsystemet. Studien företas inom rättsområdet internationell skatterätt, men har emellertid en interdisciplinär ansats. Härav analyseras även bestämmelser inom folkrätt, konstitutionell rätt, förvaltningsprocessrätt, allmän förvaltningsrätt och sekretess. The focal point of this study is mutual agreement procedures, which are found in tax treaties, and derived from Art. 25 OECD Model Tax Convention (OECD MTC). The overall purpose of the mutual agreements is to avoid international double taxation. The agreements can either constitute an alternative to court proceedings, or constitute a means for improving the functioning of tax treaties. Provisions regarding mutual agreements can be found, in various forms, in all Swedish tax treaties. Since Sweden is a dualistic state tax treaties are incorporated into the Swedish legal system by legislation. This means that the provisions regarding mutual agreements are incorporated into Swedish legislation. Legal difficulties that arise regarding the agreements are mainly due to the fact that mutual agreement procedures constitute an internationally, by the OECD, constructed phenomenon, which is to be applied on a nationally, already existing, legal system. It may hereby occur tensions and conflicts between different provisions. The overall aim of this study is to identify and evaluate mutual agreements from a Swedish perspective. This includes identifying a relatively unexplored area, i.e. mutual agreements and their place within the Swedish legal system. In order to meet the overall objective, three research tasks are formulated. First, which internal provisions apply to mutual agreements, and how are they to be applied? Secondly, it is examined if the Swedish legal system, regarding mutual agreements, is consistent from three evaluation criteria: the constitutional principles of separation of powers and legal competence, legal certainty aspects, and the provisions of the Vienna Convention of the Law on treaties (VCLT). If there are any inconsistences in the legal system, may these be solved? Thirdly, it is studied if the Swedish legal system, regarding mutual agreements, provides for fulfillment of the purpose of mutual agreements or if there are any legal obstacles to this. The thesis is carried out in the field of tax law. However, the study has an interdisciplinary approach, which means that aspects of other areas of law are considered, such as international law, constitutional law, administrative judicial procedural law, administrative law, and secrecy.
Keywords: Convention fiscale; Model Tax Convention; Mutual Agreement Procedure (MAP); Tax treaties

Tolkning och utfyllning : Undersökningar kring ett förmögenhetsrättsteoretiskt tema - Samuelsson, Joel (Iustus förlag, 2008)
This is a thesis in contract law concerning the distinction between interpretation of contracts (“tolkning”) and construction of contracts (“utfyllning”) traditionally upheld within Scandinavian doctrine. To some extent, this distinction has always been a source of conceptual confusion, but in late-modern times, it has, in certain respects, become almost unintelligible – owing to the gradual loss of function of the form of rationality that originally sustained it. The distinction is now a mere artefact. In itself, this fact does, of course, not make this particular conceptual contraption exceptional. As they are absorbed into the language of contract law, all successful contract law concepts undergoes a process of reification. In the case of the distinction between interpretation and construction, the result is, however, unusually curious. In its traditional form, the distinction expresses the hope for a law of contract that is organized according to scientific principles. It rests on the assumption that it is desirable and possible, in principle, to separate science from non-science. It presupposes that questions of fact are separable from questions of law, Is from Ought, and the uncovering of the meaning of legal documents from the application of the rules they contain. The distinction promises that it is possible to escape the confines of the law-text, to reach beyond the text and the play of words constituting its interpretation, in order to ground interpretive discourse in factual reality. Yet, the distinction itself is nothing but text, i e, nothing but law. Drawing on the Kantian tradition, specifically on the writings of Wittgenstein, the author subjects this contradictory structure to criticism. The aim of the study is, however, not to once and for all remove the contradiction. On the contrary, the policy advocated is one of acceptance – mediated through historical awareness. By distancing ourselves from the vision of law and science that is immanent in the distinction under scrutiny, we would be able to come to terms with the hermeneutical side of contract interpretation, and with the inscrutability of the subjective dimension of the contract construct. When interpretation is called for, it is due to the very fact that there is no verifiable intention, yet the conclusions of the interpreter are given in the form of reports on what the parties actually intended. This, the author concludes, does not make the interpretation of contracts unscientific, even though we, being Scandinavian private law lawyers, were fostered to think otherwise.
Keywords: Avtalsrätt; Contract law

Generalklausul mot skatteflykt - Rosander, Ulrika (Internationella Handelshögskolan, 2007)
Skatteflykt motverkas i många rättssystem genom åtgärder på olika nivåer. I Sverige är en av de metoder som används en lagstiftad generalklausul mot skatteflykt, skatteflyktslagen. Såväl rättssäkerhet som skattesystemets effektivitet anses vara grundläggande värden att upprätthålla i det svenska skattesystemet. Skatteflyktsproblematiken innebär dock att dessa båda värden i vissa situationer inte samtidigt kan uppfyllas fullt ut, vilket innebär att ett rättsligt område skapas där det blir nödvändigt att göra kompromisser och avvägningar. Det är den här balansen som är den stora utmaningen gällande åtgärder mot skatteflykt och som blir mycket tydlig gällande skatteflyktslagen. Avhandlingen analyserar generalklausuler mot skatteflykt ur ett rättssäkerhets- och effektivitetsperspektiv. Denna analys genomförs i form av en komparativ studie av Sveriges, Kanadas och Tysklands generalklausuler mot skatteflykt. Användandet av en generalklausul jämförs också med användandet av en praxismetod, vilket är den andra repressiva metoden mot skatteflykt som är frekvent förekommande i olika rättssystem världen över. Det konstateras att det är många olika frågor vid sidan av den konkreta rekvisitkonstruktionen och tillämpningsområdet som påverkar vilken rättssäkerhet och effektivitet som en generalklausul mot skatteflykt uppnår. Hur domstolssystemet ser ut, vilken inställning som finns till lagtolkning och hur domstolarna och skattemyndigheten väljer att tillämpa klausulen är exempel på mer generella frågor som har stor betydelse. Men även t.ex. relationen till andra metoder mot skatteflykt, möjligheten att erhålla förhandsbesked och vilka administrativa specialregler som används påverkar. I avhandlingen framför författaren sin uppfattning om vilka områden som är av störst vikt att utveckla i svensk rätt för att stärka skatteflyktslagens rättssäkerhet och effektivitet i framtiden.
Keywords: Fraude fiscale; Skatterätt; Tax fraud; Tax law

Licensavtalet och konkurrensrätten - Gölstam, Carl Martin (Uppsala universitet, 2007)
The purpose of this thesis is to describe and analyse the significance of economic thinking and arguments in the treatment of licence agreements in EC competition law. A central question is to what degree the concept of competition in EC law reflects an economically realistic approach to competition. The study also investigates to what degree the economic functioning of intellectual property is considered in competition regulation and how much the economic functioning of the licence agreement is considered. The investigation mainly consists of a comparative analysis of EC competition law and American antitrust law concerning the economic arguments and their importance. The treatment of territorial restrictions, field of use restrictions, quantity clauses, tie-outs, tie-ins, grant back, no-challenge clauses and price restrictions are of special interest here. This study shows that an economically realistic view of competition has influenced current EC competition law, especially in the Technology Transfer Block Exemption Regulation (TTBER). Exceptions from this development in the EC law are mainly due to the goal of integration of the common market. Territorial restrictions are strictly regulated in the TTBER even when the parties’ market shares are below the market thresholds defined in the regulation. The function of intellectual property rights are not much considered in EC competition law but there are general remarks about the economic functioning of patents in the Guidelines for the TTBER. However, it is difficult to find evidence for economic reasoning about patents in the formation of concrete rules. On the contrary, patents are weakened by the widened concept of exhaustion presented in the Guidelines. The economic functioning of the licence agreement is considered in the rules of TTBER and the economic arguments for clauses which create incentives for making investments or give the possibility of control are acknowledged. However, the free riding argument has a weak position when applied to territorial restrictions, which are more formalistically regulated. The EC competition law has become more similar to American antitrust law. The decisive difference consists in the judicial treatment of territorial restrictions, where the goal of integration is still of central importance in EC law.
Keywords: Antitrust Law; Civilrätt; Competencia; Competition law; Immaterialrätt; Intellectual property; Know-how; Konkurrensrätt; Law and Economics; Licence agreement; Licensavtal; Licensing; Patent; Private law; Rättsekonomi; Technology transfer; Tekniköverföring

Konkurrenslagen och konkurrensbegränsande offentliga regleringar - Edwardsson, Eva (Uppsala universitet, 2003)
The dissertation addresses the problem of how conflicts between the Swedish Competition Act (SFS 1993:20) and anti-competitive state regulations are to be solved. The study focuses on the legal situation in Sweden after 1993, when a new competition law was enacted and after the Swedish Membership of the European Union 1995. A comparative survey of how similar conflicts are solved in American Law, EU Law and Danish Law is made. The rationale behind the reform of the competition legislation in Sweden was the consideration that competition did not work well enough on Swedish markets. One important reason for this was thought to be the existence of regulations with a negative impact on competition. The solution of the problem was thought to reside in the adjustment of the Swedish competition legislation to the rules of the European Community (EC). After this substantial legal reform, a change in how anti-competitive regulations are dealt with could be expected. This study shows, however, that there has been practically no change at all. When conflicts between the Competition Act and anti-competitive regulations do occur, the Swedish Competition Authority evaluates the applicability of the regulation to see if a conflict really is at hand. In this legal process it is suggested that the regulation and not the Competition Act should be interpreted narrowly. This study shows that such a restrictive approach can be justified when taking the relevant sources of law into account. In cases where a disturbance to competition is the direct and necessary consequence of a clear regulation – with due considerations to EC Law – the regulation prevails. When these conditions are not at hand, it can be justified to give priority to the Competition Act.
Keywords: Competencia; Competition law; Concurrence (droit); EG-rätt; EU-rätt; Europarätt; Konkurrensbegränsande; Konkurrenslagen; Konkurrensrätt; Regleringar

Direktkrav : Om rätt att rikta anspråk mot gäldenärens gäldenär - Zackariasson, Laila (Iustus förlag, 1999)
This study has two purposes. First, it intends to clarify to what extent there is a right of direct action in Swedish law. Second, it attempts to establish the implications of different rules governing the direct action claim. The concept of direct action is used where the following conditions are fulfilled. (1) A creditor (C) is entitled to make a claim against his debtor's (D's) debtor, or the debtor of his debtor's debtor etc., or both, (against DD). (2) C's right remains the same where D (or an intermediary party) goes bankrupt or a seizure is made of the relevant claim against DD. (3) C's claim against DD does not exceed his claim against D. (4) C's claim against DD does not exceed D's (or an intermediary party's) claim against DD, or the claim that D (or an intermediary party) would have had against DD, if there had been no excuses from liability. (5) DD's performance to C will entail a corresponding reduction of C's claim against D. (6) C's right to bring action against DD is independent of (other) recognised principles of law. Analyses are made of cases where D has concluded a transaction with C on DD's behalf but in his own name or without authority, and cases where DD has, in a contract with D, assumed an obligation, which is closely linked to D's obligation towards C. The study also includes cases where a breach of contract by DD has caused a breach of contract by D against C, and cases where DD's tortious act (or omission) or breach of contract against D has caused consequential loss to C.
Keywords: Action directe; Bakre led kontraktuell kedja; Borgenärsskydd; Creditors' rights; Créance directe; Direct action claim; Direktkrav; Täckningsfordran